2014
DOI: 10.1111/1469-0691.12251
|View full text |Cite
|
Sign up to set email alerts
|

Impact of carbapenem resistance on clinical and economic outcomes among patients with Acinetobacter baumannii infection in Colombia

Abstract: Acinetobacter baumannii is a major cause of healthcare-associated infection, often affecting critically ill patients. The purpose of the study was to examine the associations of carbapenem resistance with mortality, length of hospital stay and hospital costs among patients infected with A. baumannii in intensive-care units (ICUs) in Colombia. A prospective, multicentre cohort study was conducted among 165 patients with A. baumannii infection admitted to ICUs between April 2006 and April 2010. Patients with car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 28 publications
2
26
0
Order By: Relevance
“…However, carbapenem-resistant isolates have been increasing worldwide [2,12,13,14,15]. In recent years, carbapenem resistance rates were reported to be over 50% [16,17,18,19,20,21], and in our last study it was found to be 92% in intensive care units [18]. Carbapenem-resistant A. baumannii poses a significant threat in hospitals, as therapeutic options are limited.…”
Section: Discussionmentioning
confidence: 88%
“…However, carbapenem-resistant isolates have been increasing worldwide [2,12,13,14,15]. In recent years, carbapenem resistance rates were reported to be over 50% [16,17,18,19,20,21], and in our last study it was found to be 92% in intensive care units [18]. Carbapenem-resistant A. baumannii poses a significant threat in hospitals, as therapeutic options are limited.…”
Section: Discussionmentioning
confidence: 88%
“…Study characteristics of the 16 included studies are summarized in Tables and . The sample size of studies ranged from 52 to 386.…”
Section: Resultsmentioning
confidence: 99%
“…Study characteristics of the 16 included studies are summarized in Tables 1 and 2 [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. The sample size of studies ranged from 52 to 386.…”
Section: Resultsmentioning
confidence: 99%
“…We found a higher mortality rate in both groups and our study demonstrates that patients with carbapenem-resistant A. baumannii (CRAB) infections have higher mortality than carbapenemsensitive A. baumannii (CSAB) infections, but the difference we found was not as statistically significant as that in the study by Aydemir et al Although Lemos et al reported a significant difference in the mortality rate between patients with MDR isolates and those with multidrug-susceptible isolates. 17,30 Patients with CRAB pneumonia have a higher mortality rate than that from CSAB pneumonia in Zheng et al study. 31 But we found no statistical difference between the two groups.…”
Section: Discussionmentioning
confidence: 89%